Dampen macroeconomic volatility: A useful role of capital controls on international trade - Chokri Zehri (Journal of Applied Economics, 2022)
Capital controls may adversely affect international trade. This study aims to demonstrate the usefulness of capital controls for reducing macroeconomic volatilities and then mitigating their negative effects on international trade. Using quarterly data, we applied a dynamic panel approach to a sample of 26 countries over the period 2010-2020. By diversifying the estimation techniques and using different capital control indexes, our results show that a capital control policy supports international trade and reduces exchange rate and interest differentials volatilities. The impact of capital controls is asymmetric when considering the role of financial development, the cyclical behavior of capital controls, and the simultaneous use of macroprudential policies. This study raises some policy implications, particularly, the necessary coordination and adjustment of the macroeconomic policies and the importance of targeting long-lasting controls when applying a restrictive policy.
Keywords: 330; Capital controls; channels; international trade; policy; volatility